(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Children with Down syndrome often exhibit challenging behaviors that impact their daily functioning and social interactions. Identifying these behaviors and their associated factors is essential for developing targeted interventions to enhance their well-being and quality of life. The objective of this study was to identify and assess challenging behaviors in children with Down syndrome, determine their prevalence, and evaluate the influence of comorbidities, living environment, cognitive and communication abilities, mobility status, and socioeconomic status on behavioral functioning. Methods: A cross-sectional study was conducted with a sample size of 42 children with Down syndrome age range of 5-12 years, selected using a purposive sampling technique. Data were collected through caregiver-reported questionnaires assessing behavioral challenges, including tantrums, aggravation, aggression, separation anxiety, stubbornness, and adaptability to routines. Statistical analyses included chi-square, independent t-tests and ANOVA. Results: The findings revealed that tantrums and stubbornness were among the most prevalent challenging behaviors, reported by 48% and 59.52% of caregivers, respectively. Social interaction challenges, including aggravation, were noted in 42.86% of cases. A significant portion (80.95%) of caregivers felt confident managing challenging behaviors at home. Statistical analysis demonstrated that cognitive ability, communication ability, mobility status, and socioeconomic status significantly influenced behavioral functioning (p < 0.001). Higher adaptive behavior scores were associated with mild cognitive ability, verbal communication, independent mobility, and higher socioeconomic status. Conclusion: The identification of behavioral challenges during early development requires specific interventions and empowered parents to create effective outcomes for children with Down syndrome and their families.